La seccionación en la prensa gratuita diaria de Sevilla - Gómez y Méndez, José Manuel; Méndez Muros, Sandra (Estudios sobre el Mensaje Periodístico, 2010)
Newspaper sections are usually a topic reduced to the level of writing as a well-known classifier element, which often causes scientific disinterest in the evolution analysis, exactly because it is less visible in the payment press. However, the arrival of the free of charge press makes a study field about variability in the thematic classification as the basic role of the sections. This paper focuses on the research into sections of the free of charge newspapers that are delivered in Seville, that can extend to the same dailies published in other cities, to obtain accurate conclusions on the sectioning as a way of structuration on the contents although varied journalistic approaches in a press type with different objectives.
Keywords: Sections; Free of charge press; Structuration; Sevillian press; Sectioning